The Effect of Statins on Vascular Function in Adolescents with Familial Hypercholesterolemia: A Literature Review - Wolf, Astrid De; Staels, Willem; Meerschaut, Ilse; Wolf, Daniel De; Vanbesien, Jesse; Nauwynck, Elise; Gies, Inge; Schepper, Jean De (Cardiology and Cardiovascular Medicine, 2024)
Background: Familial hypercholesterolemia (FH) is characterized by significantly elevated low-density lipoprotein cholesterol (LDL-C) levels, increasing the risk of early-onset atherosclerosis. Ultrasound studies of superficial arteries can non-invasively assess early vascular changes in children. Flow-mediated dilatation (FMD) and arterial stiffness (AS) are more sensitive indicators of early atherosclerosis than intima media thickness (IMT) as they represent the earliest functional alterations in the arterial wall. However, FMD and AS measurements are technically challenging and normative values in pediatrics vary substantially. Here, we review the literature on statin-induced vascular changes in FH. Results: Two studies investigating the effects on FMD demonstrate increased FMD levels after treatment initiation with simvastatin. Moreover, studies evaluating AS show conflicting results, with one study observing an insignificant increase in AS after fluvastatin treatment and another showing an insignificant decrease following rosuvastatin therapy. IMT changes during statin treatment vary across studies, with some showing reductions after 2 years of pravastatin treatment, while others report improvement over time with longer statin therapy. Various factors influence vascular changes during statin treatment, including LDL-C levels, gender, age, family history of premature cardiovascular disease, and lifestyle factors. Younger age at statin initiation is associated with better vascular outcomes, supporting early treatment initiation in FH adolescents. Conclusions: We highlight the importance of ultrasound studies in assessing vascular changes in FH adolescents undergoing statin therapy. Further research should aim to identify the most effective statin type and treatment targets. Assessing vascular function in the clinical management of children with FH may improve cardiovascular outcomes.